APPLYING THE THEORY OF CONSTRAINTS TO INCREASE ECONOMIC VALUE ADDED: PART 1 - Smith, Malan; Pretorius, Pieter (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: This article, presented in two parts, explains how to apply the Theory of Constraints (TOC) in a business to increase Economic Value Added (EVA). The first part deals with the theory, while the second part deals with the implementation. The goal of a business, the measurements of the goal and the priority of the measurements are discussed. The future reality of a company which implements TOC principles is shown through cause and effect to lead to an increase in EVA. The increase in EVA is caused by an increase in return on investment and a reduction in the cost of capital. The actions the company must take to increase EVA is presented. AFRIKAANSE OPSOMMING: Hierdie artikel, aangebied in twee dele, verduidelik hoe om die Teorie van Beperkinge (TVB) in a besigheid toe te pas om Ekonomiese Toegevoegde Waarde (ETW) te vermeerder. Die eerste gedeelte verduidelik die teorie, terwyl die tweede gedeelte die toepassing hanteer. Die doel van